DAMPAK PERUBAHAN HARGA PUPUK TERHADAP PERMINTAAN PENAWARAN KOPI INDONESIA - Hidayati, Dwi Ratna; Soetriono, Soetriono (Jurnal Sosial Ekonomi Pertanian, 2008)
The complexity of Indonesia and international coffee market is an interesting phenomenon to be checked. Especially in diversity of commodity coffee market. Therefore, this research take the problems of keragaan coffee market and see the existence of change when the component change in variable of former of commodity market coffee domesticly and also international happened. Result of this research is that diversity Indonesia coffee market in econometrics model determined by interaction of linkage and the influence from coffee demand factor that influenced by the amount of the coffee produce, the coffee stock, amount of the Indonesia coffee import and the tapered down with the amount of the Indonesia coffee export. Coffee’s demand was influenced by the Indonesia coffee price, the amount of the world coffee import, earnings per capita of Indonesia and tea price. The applying of fertilize price policy have an effect on by simultan to keragaan the Indonesia coffee market especially at the variables of the coffee productivity, the coffee production, coffee supply, areal wide, the coffee price, the coffee demands, the export and import of Indonesia’s coffee. The best of policy alternatif is increasing of fertilize price equal to 10%. The increasing of smaller fertilize price will assist on coffee farming if it seen from traditional coffee farmer’s side. Keywords : Coffee commodity, Coffee demand, Coffee supply, Fertilizer price.